Implementasi Pendidikan Karakter berbasis Pesantren: (Studi Kasus di Pondok Pesantren Al-Islami As-Salafy Palengaan Pamekasan) - Rofiqi . Ach. Baihaqi (Prodi PAI Fakultas Tarbiyah IAI Miftahul Ulum, 2022)
Pesantren Education is very relevant if it is associated with character education. Because Islamic boarding schools are closely related in every learning to ethical education. Pesantren is also an educational institution that 24 hours a day always teaches role models from the 'ulama' who exist as an inseparable part of the existence of Islamic boarding schools. This study uses a qualitative approach with a phenomenological type of research through several data collection techniques, namely: interview, observation and documentation techniques. This study shows that the implementation of character education at the Al-Islami As-Salafy Islamic Boarding School in Taman Sari Palengaan Pamekasan is highly emphasized by means of total coaching for 24 hours. So that students get used to doing good things, from getting up from bed to sleeping again. Starting from how to dress, interact, eat, exercise, to worship, both obligatory and sunnah. There are several methods used by the Taman Sari Islamic Boarding School to build the character of the santri. First, the Sorogan Method. Second, Wetonan Method. Third, the Muhawarah Method. Fourth, the Muhawarah Method. Fifth, the Majlis Ta'lim Method. Sixth, the Discussion Method. While the character values ​​that are instilled from interaction and learning. First, the religious character, namely where students are required to pray five times a day, and Tadaarus al-Quran, there are suggestions for fasting, Duha prayer and so on. Second, be honest. Third, Tolerance. Fourth, Discipline. Fifth, work hard and be independent. Sixth, Curiosity. Seventh, the spirit of nationalism or nationalism. Eighth, communicative. Ninth, love to read, tenth, love to read, and responsibility.